A chromosomal reference genome sequence for the northern house mosquito, Culex pipiens form pipiens, Linnaeus, 1758 [version 1; peer review: 2 approved] - Jonathan M.D. Wood; Mara K N Lawniczak; Yuki Haba; Jenny C Hesson; Edel Sheerin; Carolyn S McBride; Damon-Lee B Pointon; Thomas C Mathers; Cibin Sadasivan Baby; James W Torrance; Shane A McCarthy; Alex Makunin; et al. (Wellcome Open Research)
We present a genome assembly from an individual female Culex pipiens sensu stricto (the northern house mosquito; Arthropoda; Insecta; Diptera; Culicidae), from a wild population in Sweden. The genome sequence is 533 megabases in span. Most of the assembly is scaffolded into three chromosomal pseudomolecules. The complete mitochondrial genome was also assembled and is 15.6 kilobases in length.